Dampak Investasi Portofolio Terhadap Nilai Tukar di Indonesia - Wahyuni, Asri; Satria, Doni (Media Riset Ekonomi Pembangunan (MedREP), 2024)
The objective of this research is to analyze the influence of foreign capital flows, especially foreign portfolio investment, in influencing the exchange rate in Indonesia. This research uses secondary data sourced from the World Bank Indicator and Bank for International Settlements (BIS) with the main independent variables being foreign portfolio investment and the control variables in the research, namely foreign direct investment, interest rates and inflation and the dependent variable, namely the exchange rate. This research uses multiple regression analysis with time series data from 1991-2020. The results of the analysis found that foreign portfolio investment plays an important role in influencing the exchange rate in Indonesia. However, it has not been able to provide a positive contribution in encouraging the strengthening of the exchange rate in Indonesia. So, the government and monetary authorities need to pay attention to important factors that influence foreign capital flows, especially foreign portfolio investment, namely transaction costs, government restrictions, product specialization or other factors to encourage the strengthening of the exchange rate in Indonesia through foreign portfolio investment.